RESEARCH OF THE DEVELOPMENT OF SPIRITUAL AND MORAL COMPETENCIES OF FUTURE TEACHERS - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
Measures aimed at forming a harmonious generation, educating young people spiritually and morally, and making them active participants in the ongoing reforms are being consistently implemented. Increasing professionalism and competence have been identified as key drivers of progress and activities leading to Sustainable Development Goals. The modern educational system involves the further improvement of the mechanisms for increasing the competence of future professionals based on a creative approach and an innovative system of practical implementation. From this point of view, the research competence of future professionals based on a creative approach is of particular importance for the creation of innovations, and the creation of intellectual resources for socio-economic development through the development of cognitive and divergent thinking based on modern pedagogical procedures that generate new knowledge. and expanding training opportunities for competition personnel. The article deals with the requirements and guidelines for responsible teachers.